OPTIMALISASI LAHAN KURANG PRODUKTIF DALAM RANGKA MENDUKUNG KETAHANAN PANGAN MELALUI PEMBERDAYAAN MASYARAKAT KOTA - Jajuk Herawati; Dwie Retna Suryaningsih; M. Thohiron; Ken William; Habib Habib (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
The Faculty of Agriculture, Wijaya Kusuma University, Surabaya has established an ongoing partnership through the Community Service Program where one of the fostered partners is the "SATU PADU" Farmer Group in the Jambangan sub-district area, Surabaya city. These partners provide guidance through mentoring various innovative agricultural activities oriented towards optimizing urban land by students or lecturers in the FP-UWKS scope to contribute as a solution to the problem of food security in the city of Surabaya. Community Service Activities in an effort to optimize less productive land for sustainable food security in the Jambangan Village, Surabaya City, East Java. The implementation of the partnership program was motivated by the economic impact of the post-Covid-19 pandemic which was very concerning and was felt at the household scale. Therefore, this activity aims to optimize land use in the environment around the area where people live. The specific target is limited and less productive land through environmentally sound utilization innovations to increase family economic income in a sustainable manner. The Community Partnership Program in the Jambangan Village, Surabaya City uses the Participatory Rapid Rural Appraisal (PRRA) and Rapid and Rural Appraisal (RRA) methods which in their implementation provide opportunities and space for joint involvement between Higher Education Institutions as executors from the planning, implementation to evaluation stages. implementation of activities as effectively as possible